Price Policy, Agrarian Structure, and Rural Welfare: An ARDL Analysis of Rice Governance and Farmer Exchange Rates in Indonesia - Punguan Hutagalung; Surya Abadi Sembiring; Iskandarini Iskandarini (Universitas Pattimura, 2026)
This study investigates the impact of the Government Purchase Price (HPP) policy and fertilizer subsidies on rice production and farmer welfare, measured by the Farmer Exchange Rate (NTP), within the framework of agrarian governance in Indonesia. It examines both short-run and long-run effects while situating these policies within broader state intervention dynamics. A quantitative approach is employed using the Autoregressive Distributed Lag (ARDL) model on monthly time-series data from January 2020 to December 2024, complemented by a qualitative review of policy regulations. The findings reveal that HPP significantly affects rice production in both the short and long term, albeit with a negative coefficient, indicating structural adjustment toward equilibrium. In contrast, fertilizer subsidies show no significant effect on production, reflecting implementation inefficiencies. Regarding welfare, HPP exerts a positive and significant influence on NTP, highlighting its role in enhancing farmers’ purchasing power, whereas fertilizer subsidies remain insignificant. This study contributes by integrating production and welfare analysis within a single empirical framework and reinterpreting econometric findings through a state–society relations lens. It concludes that output price policies are more effective than input subsidies, although their impact remains constrained by institutional and governance challenges.